2005
DOI: 10.1037/0894-4105.19.6.814
|View full text |Cite
|
Sign up to set email alerts
|

A Convergent-Divergent Approach to Context Processing, General Intellectual Functioning, and the Genetic Liability to Schizophrenia.

Abstract: Convergent and divergent validity are critically important in developing psychological measures that reveal interpretable deficits in disordered populations. This article reports on 2 studies that evaluated the validity of context processing measures. In Experiment 1, a confirmatory factor analysis of data from 481 healthy adults established the convergent validity of 2 context processing measures and showed that context processing accounted for significant amounts of variance in standard IQ and working memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
88
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(101 citation statements)
references
References 42 publications
9
88
0
4
Order By: Relevance
“…The pairings of characters, objects, and preferences were all counterbalanced. The target and nontarget buttons appeared only with the presentation of each probe; therefore, subjects responded only to probes, as in other versions of the expectancy AX-CPT (39,40), preventing premature responses.…”
Section: Procedurementioning
confidence: 99%
“…The pairings of characters, objects, and preferences were all counterbalanced. The target and nontarget buttons appeared only with the presentation of each probe; therefore, subjects responded only to probes, as in other versions of the expectancy AX-CPT (39,40), preventing premature responses.…”
Section: Procedurementioning
confidence: 99%
“…As in MacDonald et al (2005) study, the 40 trials of each block consisted of 28 (70%) AX trials, 5 (12.5%) AY trials, 5 (12.5%) BX trials, and 2 (5%) BY trials. The error rate of the BX and BX-AY (the error rate of BX minus the error rate of AY) was used as the main measurements because previous studies showed that, compared with healthy controls, both SCZ patients and their healthy relatives showed significantly higher error rates in BX condition and a tendency of making less AY than BX errors thus higher value of BX-AY (MacDonald et al, 2003(MacDonald et al, , 2005.…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…The DPX task was first introduced by MacDonald et al (2005) and was shown to have adequate reliability . The DPX task in this study was presented in 4 blocks of 40 stimulus pairs (the cues and the probes) that were presented sequentially in the center of a 14-inch screen.…”
Section: Cognitive Tasksmentioning
confidence: 99%
“…Goal maintenance has been assessed by either the original AX-CPT task or its revised versionFthe dot pattern expectancy (DPX) task, which used spatial dot patterns as stimuli ). Previous studies found that both SCZ patients and their healthy relatives or siblings showed impaired performance at the DPX task (MacDonald et al, 2005;MacDonald et al, 2003), indicating that this task may also be a possible intermediate phenotype. The current study used both the N-back and the DPX tasks and hypothesized that the clinical risk allele of rs1006737 would be associated with poorer working memory.…”
Section: Introductionmentioning
confidence: 99%